Kategori dan Ekspresi Linguistik Wadah Berbahan Dasar Bambu dalam Masyarakat Jawa - Kajian Etnolinguistik - Akhmad Dzukaul Fuad; Shendy Andrie Wijaya; Gandung Wirawan (Jurnal Sosial Humaniora, 2018)
This study aims to describe the form of the lexicon in the Java language (bJ)which has the meaning of bamboo-based container. The description is basedon the formation of the lexicon, not necessarily formed and spoken withoutconsidering the external aspects of the language (metalanguage) that hasexisted in the community of speakers. The meta-language that became thestarting point and the basis of categorization makes this research not onlyinvolves linguistic analysis but a combination of linguistics andanthropology. It is commonly called ethnolinguistic. The lexiconcategorization of bamboo-based containers in Javanese is adapted to theform, the domain of use and the meta aspects of the language reflected ineach lexicon. It resulted in three domains of use and overall lexicon nouns.